Risky sexual practices among men who have sex with men in Northeast Brazil: results from four sequential surveys - Gondim,Rogério Costa (2009)
This paper focuses on recent trends in risky sexual practices for HIV/AIDS among men who have sex with men (MSM) in Fortaleza, Ceará State, Brazil. Four cross-sectional surveys were conducted (1995, 1998, 2002, and 2005) among MSM 14 years or older who reported oral or anal sex in the previous 12 months. Sexual practices were considered risky whenever the respondent reported unprotected receptive or insertive anal intercourse in the six months preceding the interview. Different selection techniques were used to recruit the study population: snowball (1995, 1998, 2002 - 32%); time-space sampling (2002 - 68%); and respondent-driven sampling (2005). Analyses were based on the comparison between proportions. High rates of risky sexual practices were reported in 1995 (49.9%), decreasing in 1998 (32.6%), increasing again in 2002 (51.3%), and showing the lowest level in 2005 (31.4%). Participants with more schooling increased their risky practices from 1998 to 2002, decreasing in 2005. Among individuals with medium or low schooling, risky behavior declined from 2002 to 2005. The article highlights the need for behavioral surveillance to properly address STD/HIV prevention.